Vostochnyĭ beregʺ poluostrova Kamchatki otʺ paralleli 58°05' do bukhty Karaga sʺ ostrovomʺ Karaginskimʺ po opisi Gidrograficheskoĭ Ėkspedit︠s︡īi Vostochnago okeana 1920 godʺ / Chertilʺ Kap. mal. pl. M. Vishkarevʺ - Russia. Glavnoe gidrograficheskoe upravlenīe (Vladivostok : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; Владивосток : [Морское министерство, Главное гидрографическое управленіе], 1920)
"Masshtabʺ 1/219156 ili 2609 s. (3 milʹ) v di︠u︡ĭmi︠e︡ po paralleli 58°45'" = Scale 1/219156 or 2609 fathoms (3 miles) in 1 inch on the 58°45' parallel.; Title translation: Eastern coast of the Kamchatka Peninsula on the 54°35' parallel from Karaga Bay with Karaginsky Island, according to the survey of the Hydrographic Expedition of the Eastern Ocean of 1920.; Relief shown by form lines, hachures and spot heights. Depths shown by soundings.; Includes table of coordinates.; Greenwich meridian.; "No. 419" -- Top right margin Grayscale; 1:219,156